EFIKASI PENGGUNAAN SENYAWA KURKUMIN DALAM EKSTRAK Curcuma longa L. SEBAGAI TERAPI ALTERNATIF GANGGUAN DEPRESI: Systematic Review - Nabilah Nurul Fitri, (2021)
Depression is a psychiatric disorder with a prevalence rate that increased to 57.6% during the COVID-19 pandemic. One alternative therapy that has been researched and assessed to have various effects in reducing symptoms of depression is the compound curcumin in Curcuma longa L extract. This study aims to determine the efficacy of using curcumin compounds in Curcuma longa L extract as an alternative therapy for depression. This research design uses a systematic review. The literature search in this systematic review was carried out on four different journal databases, namely PubMed, Prime Pubmed, ScienceDirect, and EBSCO using the 2015 PRISMA-P method covering articles from March to May 2021. There were twenty studies that met the research inclusion and exclusion criteria. . The results showed that curcumin at a dose of 100 mg/kg in in vivo trials and 250 mg in clinical trials had significant efficacy and potential as an alternative therapy in depressive disorders. This curcumin compound provides significant changes in improving depression-like behavior in rats through modulating neurotransmitter effects, reducing proinflammatory cytokines, increasing BDNF, reducing cortisol levels, and curcumin being able to improve depressive disorders in patients in clinical trials.